Fragilidade e risco de quedas em idosos de uma unidade de atenção primária à saúde - Dodt, Ana Claúdia Camurça de Fontes (2019)
Populational aging is a phenomenon that occurs in every part of the world, thus generating changes in the epidemiological profile and the occurrence of events such as fragility, chronical disease and falls. Among researchers and health professionals it is unquestionable that fragility and falls lead to a negative impact in the life of old people, their families, caregivers and society. To analyze the fragility level and falls’ risk in old patients, treated at a Primary Health Care Unit. An observational and transversal study, with a quantitative approach of 145 elderly people, was carried out in a Health Care Unit, in Fortaleza, Ceará. Data collection was developed from March to May 2018. The instrument used to identify the socio-economic variables and risk factors to Health was the Edmonton Frail Scale. The EFS was used to determine the fragility levels and the Time Up and Go – TUG to determine fall’s risks. In the elderly sample there was a female predomination, with an average age of 71 years old, presenting low scholarity, with family income around 1,5 minimum wages. Arterial hypertension and diabetes mellitus prevailed as chronical diseases among them. As to the frail level, light frail prevailed, followed by moderate and severe frail. The medium risk of falls obtained higher percentages followed by the low risk. Conjugal situation, age, comorbities, humor, polypharmacy, hospitalization and functional independence are factors related to frail syndrome and falls’ risk in old people. According to the results found at the research, it can be seen the importance of the elderly characterization as to fragility and falls risks in Primary Attention. This knowledge is necessary to assist the work of health professional in the planning of interventions and strategies to minimize or reduce the elderly vulnerabilities and risks related to these events. The incorporation of this practice in the elderly integral care will direct actions to an amplified approach of health care, prioritizing the search for autonomy and functional capacity of aged people despite any level they may present.